The Contribution of Manggar Warak Dance in Building Multicultural Education - Atip Nurharini; Muhammad Jazuli; Hartono Hartono; Eko Sugiarto (Universitas Negeri Semarang, 2021)
Culture is related to customs, habits, and works used as the process of creating dance. The Manggar Warak dance created by Yoyok Priyambodo from the Greget studio represents the culture of Semarang City. The purpose of this research is to examine the contribution of Manggar Warak Dance in building multicultural education. This study uses qualitative research methods, with an etnochoreology approach. The results shows that the Manggar Warak dance was originated from the acculturation of Javanese, Arabic, and Chinese cultures in Semarang that took a long time to cultivate to form varied dance movement patterns. It was also created based on the development of traditional dance. This dance contains the rules of dance forms and movement techniques, Javanese, Chinese, and Arabic cultures. Nowadays, Semarang's cultural heritage in traditional community life is still believed to have guiding values ​​that must be introduced, taught, and passed down to the next generation, namely 1). religious values, 2). moral values, 3). social value, 4). cultural values ​​and 5). aesthetic value in social life. Appreciation of dance can be used as an inner exercise for some people so they can find philosophy inside the dance. It is one of the value implementations from the Manggar Warak dance function which provides moral development and noble soul. In conclusion, we can introduce multicultural values ​​through the Manggar Warak dance as a guiding value to develop character and behavior that shows good and bad things.